2002
DOI: 10.2118/02-06-05
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Hydraulic Models for Foam Drilling

Abstract: Compared to conventional (incompressible) drilling fluids, relatively little is known about the hydraulic and rheological properties of foamed drilling fluids. The complex flow mechanisms involved in compressible drilling fluid circulation make determination of the optimum combination of liquid and gas injection rates very difficult. Modelling of foam rheology is the key issue in hydraulic design, in order to predict the bottom-hole pressure accurately, and to optimize the different controllable variables for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Pipe viscometers were used in most of these studies to characterize flow behavior of foams. Other studies (Ozbayoglu et al, 2000;Ahmed et al, 2003b) focused on topics like hydraulic performance of foam under different conditions. In addition, rheological properties of foams with different viscosifying additives were investigated (Harris, P.S.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Pipe viscometers were used in most of these studies to characterize flow behavior of foams. Other studies (Ozbayoglu et al, 2000;Ahmed et al, 2003b) focused on topics like hydraulic performance of foam under different conditions. In addition, rheological properties of foams with different viscosifying additives were investigated (Harris, P.S.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This specific (critical) point depends up on the liquid phase composition and its rheological properties. Ozbayoglu et al (2000) investigated different foam hydraulic models (Beyer et al, 1972;Blauer and Kohlhaas 1974;Sanghani and Ikoku 1983;Gardiner et al, 1998;and Valko and Economides 1992) developed over the years to assess their accuracy. Model predictions were compared with their experimental results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozbayoglu et al [85] carried out a comparative study of the foam hydraulic models. They suggested that foams can be modeled as a power law fluid when the foam quality is 70-80% and as a Bingham plastic fluid when the foam quality is 90%.…”
Section: Foam Rheologymentioning
confidence: 99%
“…Ozbayoglu et al (2002) showed that, no bbestQ rheological model existed to explain the rheological behavior of foam for all quality ranges. Therefore, generalized rheological model parameters, N and KV, are preferred to explain foam behavior in this study, where N and KV are functions of foam quality as well as the conduit geometry where the flow takes place.…”
Section: Foam Rheologymentioning
confidence: 99%